Comparative genomic epidemiology of food- and patient-derived diarrheagenic Escherichia coli from sentinel surveillance in Southeast China - Xiaomeng Huang; Li Gong; Fuming Liu; Jianhua Mei; Jinkai Li; Siyu Fu; Liyang Qiu; Deyong Zhang; Xiuying Chen (International Journal of Food Microbiology, 2026)

Ethical risks and considerations of brain-controlled and neuromodulation technologies - Kaifeng Huang; Hengyuan Yang; Shixuan Zhu; Yanxiao Chen; Tianwen Li; Lei Zhao; Anmin Gong; Wenya Nan; Jiaping Xu; Yunfa Fu (Cognitive Neurodynamics, 2026)

Trading time for space: a new approach to investigate the EEG neural mechanisms of fine motor brain based on ICA-optimized traceability network analysis - Anmin Gong; Huijie Man; Xinyu Shi; Sinan Li; Xiuyan Hu; Bowen Gong; Ting Shi; Yunfa Fu (Cognitive Neurodynamics, 2026)

Single-cell transcriptomics reveals heterogeneous stress responses and Mg2+-mediated survival mechanisms in Lactobacillus delbrueckii subsp. bulgaricus during freeze-drying and storage - Liang Liu; Jing Ren; Zhongxia Li; Xinyue Hao; Can Di; Zixin Fu; Liang Li; Xiaolei Ze; Ruikun He; Lanwei Zhang; Pimin Gong (Food Research International, 2026)

High-performance Ti3C2-mediated adsorptive membrane for selective lithium recovery from shale gas wastewater - Dandan Zhao; Feiyang Yuan; Yuchun Ren; Yan Li; Keji Zhou; Xiaoying Huang; Chen Fu; Zhengjun Gong (Desalination, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Divergent controls of climate and chemical traits on the decomposition of leaf litter, fine roots, and coarse roots: a global synthesis - Xiaoxiang Zhao; Qiuxiang Tian; Siying Gong; Anders Michelsen; Li Xiao; Lihua Fu; Yan Yang; Rudong Zhao; Liang Chen; Feng Liu (CATENA, 2026)

Binocular-depth-guided dual-view camera-LiDAR fusion for kiwifruit pose estimation in robotic harvesting - Shiao Niu; Leilei He; Qilin Gong; Qichen Huang; Ruichao Luo; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Anastasia Grecheneva; et al. (Computers and Electronics in Agriculture, 2026)

Edible Medicinal Choerospondias axillaris Polysaccharides: A Review on Extraction, Structure–Activity Relationships and Encapsulation Properties - Caijiao Li; Huijie Zhang; Yan Gong; Lei Fu; Jin Ma; Meng Wang (Food Bioscience, 2026)

Prenatal exposure to residential greenness and artificial light at night and neurodevelopmental outcomes in children aged 4–12 years: A retrospective cohort study in China - Jian Chen; Daosen Wang; Jiaxuan Fu; Ranran Gong; Qifei Chen; Jie Tang; Ziyu Feng; Han Li; Xinyun Lin; Xiuhong Li (Environmental Research, 2026)

Dynamic chromatographic separation of Yb3+/Lu3+ using a P507-functionalized polymeric resin for high-purity 177Lu production - Yanli Li; Xin Wang; Rao Fu; Zhaolong Niu; Hengyi Gong; Kun Zhou; Peizhuo Hu (Chemical Engineering Journal, 2026)

Glucose- and pH-responsive nanozyme-integrated hydrogel with enzyme-like activity for MRSA infected diabetic wound healing - Pengchao Zhao; Dianhao Gong; Zhihui Ma; Huiying Yu; Xin Li; Zhixuan Li; Zimeng Xu; Yu Cao; Fangfang Fu; Chunshan Quan; Kun Lei (Chemical Engineering Journal, 2026)

From Geoheritage to Rural Revitalization: A Case Study of the Ru’an Geo-Cultural Village in Hainan Province, China - Jianweng Gao; Zhenliang Wang; Jingjing Gong; Jianzhou Yang; Yan’gang Fu; Lujun Lin; Zhuang Duan; Keqiang Zhao; Yong Li (Geoheritage, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Highly stable MOF-based dual-functional membranes for solar steam evaporation and oil-water separation - Shiyu Fu; Xiaoling Kang; Huimin Wang; Zheng Wang; Binjie Li; Jiang Gong; Xu Peng; Zhiyue Dong (Chemical Engineering Journal, 2026)

Urinary DNA Methylation Profiling Improves Discrimination of Prostate Cancer Across PSA-Defined Risk Strata - Wei Zhu; Yi Qian; Xiaokai Zhao; Zhenxuan Fang; Zeyu Luo; Wenhua Xie; Yifang Cao; Wei Chen; Huiyu Fu; Jiayu Peng; Lijun Zhang; Jieyi Li; et al. (Biochemical Genetics, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

High-resolution mass spectrometry reveals escalating concentrations of organophosphate esters in Yangtze River Basin soils along the upstream-to-downstream transect - Shuai Gong; Jianan Huang; Jianhua Li; Guanyong Su; Pingqing Fu (Environmental Pollution, 2026)

Resolving multi-metal encapsulation in coal gasification slag via an integrated activation and selective-separation strategy - Xiaoye Hong; Min Fu; Yanbing Gong; Qiqi Li; Zhe Sun; Yongfeng Zhang; Yinmin Zhang; Xiang He (Chemical Engineering Journal, 2026)

Neurovascular decoupling is associated with altered glymphatic function as assessed by the DTI-ALPS index in patients on dialysis - Wenbo Yang; Lijun Song; Mingan Li; Xiaoyan Bai; Boyan Xu; Min Li; Zhenghan Yang; Tiantian Ma; Yong Gong; Gang Fu; Wenjing Zhao; Jing Zhao; et al. (Brain Imaging and Behavior, 2026)

Establishing PdHg dual-atom sites on defective nitrogen-doped framework activated carbon for effective electrochemical CO2 reduction - Yanlong Gong; Fanfang Meng; Xiaoli Ran; Shixian Xiong; Jiangcheng Li; Xiaohong Yang; Haitao Fu; Xizhong An (Fuel, 2026)

Ultrasound-activated in situ nano-vaccines (SATNAV) for precise CRPC sono-immunotherapy via multi-reprograming the immunosuppressive microenvironment - Xinzhi Xu; Jing Fu; Yujie Wan; Jiaqi Gong; Ruixia Hong; Jia Tang; Qizhi Wang; Ying Li; Kaifeng Huang; Yizhe Zhong; Hang Zhou; Jichun Yang; et al. (Chemical Engineering Journal, 2026)

Exogenous plant growth-promoting rhizobacteria boosting photosynthetic efficiency via thylakoid lipid restructuring in potato under low-potassium conditions - Xin Zhou; Xin Cheng; Baoyu Fu; Meiling Li; Chao Luo; Haoyang Gong; Hongkun Yang; Jingye Fu; Chengcheng Cai; Kaiqin Zhang; Shunlin Zheng (Plant Science, 2026)

Construction of Kongyu 131 mutant library provides genetic resources for rice functional genomics and germplasm improvement - Tingting Xu; Qun Yang; Ran Li; Jianping Wang; Zhishan Luo; Daoyong Gong; Leihao Weng; Xiaoshan Huang; Debao Fu; Jing Li (Plant Science, 2026)

pH-responsive nanocomposite hydrogel for treating diabetic periodontitis via catalytic therapy, antibacterial and osteogenic synergistic effects - Mengqing Gong; Fangze Guo; Heyi Zhang; Shang Tang; Qingao Wang; Yabo Li; Changqing Yuan; Qinrui Fu (Chemical Engineering Journal, 2026)

Design and synthesis of novel fucosylated chondroitin sulfate derivatives as intrinsic FXase inhibitors and evaluation of their antithrombotic activities - Dongliang Xu; Xi Gong; Lisha Lin; Hang Dong; Yijian Wen; Yingnian Li; Gang Fu; Yuanhang Ma; Weicheng Xiong; Tianyu Guan; Ao Sun; Xiangbao Meng; et al. (Carbohydrate Polymers, 2026)

Promoting soybean emergence and growth in seasonally frozen soil regions: The regulatory role of biochars on water-soil environment during freeze-thaw cycles - Yidan Gong; Zhiyong Gao; Qiang Fu; Jing Li; Tianxiao Li; Renjie Hou (Soil and Tillage Research, 2026)

A large-scale framework for deriving tidal flat topography from SWOT data - Hao Xu; Nan Xu; Wenyu Li; Kai Tan; Chunpeng Chen; Huan Li; Lucheng Zhan; Pei Xin; Jiaqi Yao; Peng Li; Zhen Zhang; Haipeng Zhao; et al. (Remote Sensing of Environment, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Investigating the failure mechanism of a landslide triggered by the combined effects of excavation and rainfalls through numerical approaches - Shu-wei Sun; Xin-yu Fu; Yuan Li; Qiang Wen; Run-jie Gong (Landslides, 2026)

PRSGNet: A robust framework for crop row detection in complex field scenarios - Dengbin Fu; Yinghu Cai; Zhanpeng Liang; Zhenyu Tang; Zhiqiang Yao; Hao Gong; Renjun Hu; Jiating Li; Long Qi (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Quantifying internal phosphorus loading based on high-resolution porewater monitoring and machine learning in the eutrophic Lake Taihu - Youzi Gong; Yan Wang; Yi Zhang; Shi Fu; Shuaishuai Gao; Askar Akida; Ziyi Xiong; Shuhang Wang; Xia Jiang; Xianfang Fan; Musong Chen; Yongjiu Cai; et al. (Journal of Environmental Sciences, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

The role and therapeutic potential of purinergic signaling pathway in metabolic syndrome-related atherosclerosis - Xiang Li; Chengxin Gong; Chengxiao Fu; Qing Xia; Yue Zhang; Yue Du; Yuting Sun; Hong Xu (Purinergic Signalling, 2026)

Enhanced LSHADE-SPACMA with fitness-directed selection pressure mutation and elastic archive for UAV trajectory planning and PV parameter identification - Wenhao Mao; Shengwei Fu; Guozhang Zhang; Haisong Huang; Guangming Gong; Yulu Liu; Honghai Fu; Yinwei Li; Yongpeng Zhao; Langlang Zhang; Jiawei Wang (Swarm and Evolutionary Computation, 2026)

FeSe2 graphite intercalation compounds derived from spent graphite with spatial confinement effect enable high-performance sodium storage - Jiahao Yang; Chong Xu; Zizheng Zhou; Guang Ma; Shuang Liu; Dongyuan Zhang; Gong Cheng; Junjie Fu; Sai Che; Yan Jia; Yongfeng Li (Chemical Engineering Journal, 2026)

Atomically dispersed Pd on WO3/WS2 nanoflowers for fast hydrogen detection - Jingyun Li; Fanfang Meng; Mei Zhu; Hao Lv; Yanlong Gong; Xiaohong Yang; Jiangcheng Li; Shixian Xiong; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2026)

A recyclable magnetic biochar from corn cobs and red mud for treating complex contaminants containing dyes and heavy metals - Ruihui Gong; Huidong Li; Yuxin Liu; Jiangzhe Fu (Environmental Geochemistry and Health, 2026)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Synergistic Enhancement of Cobalt Adsorption by Graphitization and Magnetic Modification of Biochar: Synthesis, Characterization, Performance and Mechanism - Hui Liu; Chen Li; Zhichao Fan; Zhirui Dou; Beibei Lu; Xiao Fan; Xiaohui Ji; Jinlong Lai; Qian Fu; Songlin Gong; Xinna Wang; Jie Liu (Water, Air, & Soil Pollution, 2025)

Applications and interrelationships of brain function detection, brain–computer interfaces, and brain stimulation: a comprehensive review - Yuhang Xue; Yanxiao Chen; Fan Wang; Lei Zhao; Tianwen Li; Anmin Gong; Wenya Nan; Yunfa Fu (Cognitive Neurodynamics, 2025)

Bioinspired urchin-like AuMnCu nanoreactors: Integrating tip-enhanced electric fields with alloy-tuned interfacial electron for precision photothermal immunoassays - Weijie Gong; Yuechun Li; Bangfeng Fu; Jinrui Shan; Jing Zhou; Sijie Liu; Jing Sun; Leina Dou; Jianlong Wang (Analytica Chimica Acta, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

Preparation of novel multifunctional magnetic biochar integrating adsorption and degradation and application in printing and dyeing wastewater - Ruihui Gong; Huidong Li; Yuxin Liu; Jiangzhe Fu; Junming Yi; Dongsheng Feng (Journal of Contaminant Hydrology, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

miR-2400 promotes proliferation of bovine skeletal muscle-derived satellite cells by regulating MAGED1 genes expression - Li Yang; Hai-Jing Luo; Zhi-An Gong; Wen-Tian Zhang; Jing-Xuan Cui; Xue-Peng Fu; Wei-Wei Zhang (Journal of Muscle Research and Cell Motility, 2025)

Delta-scale mapping of coastal erosion vulnerability at the modern Yellow River Delta and implications for geomorphic sustainability - Hongyu Ji; Xuelei Gong; Yaoshen Fan; Yuanbin Fu; Hanghang Lyu; Peng Li; Yin Cao; Shenliang Chen; Shentang Dou (Ocean & Coastal Management, 2025)

Sources and dynamics of nitrate in groundwater in a crystalline terrain of tropical Sri Lanka based on a dual isotope approach - Charitha Udeshani; Fu-Jun Yue; Yao-Qi Gong; Si-Liang Li; Rohana Chandrajith (Water Research, 2025)

Ferulic acid concentration in 233 maize inbreds and its processing stability in selected high-ferulic-acid lines - Xue Gong; Yuan Li; Li Liu; Jindong Fu; Zhonghu He; Liang Li; Wenfei Tian (Food Chemistry, 2025)

Inhibitory effects of flavonoids and alkaloids from the traditional antihyperglycemic herb Polygonatum kingianum var. grandifolium on α-glucosidase activity - Qing-Dong Ma; Xu-Juan Fu; Xiao-Qin Xiong; Dong-Mei Liu; Zhuo-Jun Li; Wei Gong; Dong-Qin Guo; Dong-Yang Yi (Natural Product Research, 2025)

Mechanistic insights into the dynamic evolution processes of LiFePO4/C batteries - Xingmin He; Kai Sun; Yi He; Xueyan Li; Kang Fu; Zhiyuan Zhang; Lili Gong; Shuai Zheng; Peng Tan (Chemical Engineering Journal, 2025)

The nuclear receptor gene SfE75 regulates the molting of Sogatella furcifera - Yi-Ming Wang; Yan-Yu Wang; Ming-Fu Gong; Shi-Yan Zhang; Jiang-Ling Chen; Xin Li; Cao Zhou; Hong Yang (Journal of Asia-Pacific Entomology, 2025)

Immobilizing PdCd dual-atom sites on rhombic dodecahedral nitrogen-doped carbon matrix for enhancing electrocatalytic CO2 reduction reaction - Yanlong Gong; Xiaoli Ran; Xiaohong Yang; Shixian Xiong; Feng Gu; Shufen Wang; Jiangcheng Li; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2025)

Method for planning subarea emission reduction strategies to improve ozone over a large area: A case of Taiwan - Tu-Fu Chen; Xin-Li Gong; Chang-You Tsai; Ken-Hui Chang (Atmospheric Environment, 2025)

An Ecosystem-Based Approach to Evaluating Impacts of Fisheries Management on Ecosystem Restoration in a Chinese Subtropical Yangming Reservoir - Haibo Gong; Chengjie Yin; Jinxiang Yu; Jun Xiao; Zhijie Yu; Xuejun Fu; Bin Huang; Xiya Wu; Caigang Li (Fishes, 2025)
This study delves into the ecological implications of diverse fishery patterns on aquatic ecosystems, centering on environmental parameters, species richness, and nutrient dynamics. Using the ecological fishery management model of Yangming Lake as a case, it evaluates its influence on water quality improvement, species diversity promotion, and ecosystem stability maintenance. From 2018 to 2022, the Shannon–Wiener index in Yangming Lake increased by 17.34%, and water quality significantly improved, with phytoplankton biomass decreasing by 95.5%, total nitrogen content dropping by 33.69%, and permanganate index declining by 30.75%. Although ecological fisheries demonstrate certain effectiveness in tackling invasive species, further in-depth research is needed. This study emphasizes the importance of striking a balance between fishery development and ecological protection, in line with the United Nations Food and Agriculture Organization’s “blue transformation” strategy. Our findings offer valuable insights for sustainable fisheries development and highlight the necessity of customized management strategies to protect biodiversity and ecosystem resilience. Future research will focus on exploring the long-term ecological effects of ecological fisheries and the role of native carnivorous fish in controlling invasive species.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Microplastics in groundwater: Environmental fate and possible interactions with coexisting contaminants - Shengfeng Liu; Chengcheng Li; Jochen Bundschuh; Xubo Gao; Xing Gong; Huihui Li; Mengyun Zhu; Ling Yi; Wenxuan Fu; Fengze Yu (Environmental Pollution, 2025)

Two new compounds from Pentadesma butyracea and their biological activities - Yue Yang; Li Hua Gong; Fu Hua Peng; Tao Jiang; Jian Guo Hu; Hong Dong Liu; Bin Li; Yin Xia Yang; Jing Ying Peng; Xue Mei Gao (Phytochemistry Letters, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

Incorporating Drought Thresholds Improves Model Predictions of Autumn Phenology in Tropical and Subtropical Forests - Yue Xu; Mingwei Li; Zitong Jia; Yufeng Gong; Xiran Li; Yongshuo H. Fu (Global Change Biology, 2025)
Drought dramatically influences vegetation phenology, thereby impacting terrestrial carbon and water cycles. However, the mechanisms by which drought drives changes in autumn phenology remain unclear, hindering the accurate simulation of these processes in phenology models. In this study, we employed ridge regression analysis to quantify the dynamic effects of intensifying drought on the end‐of‐photosynthetic‐growing‐season (EOPS) and identified the drought threshold at which the vegetation's response to drought shifts. We demonstrate that the response of EOPS in tropical and subtropical forests reverses from a delay to an advancement as drought intensity surpasses specific thresholds, with the average drought threshold across the study area corresponding to a standardized precipitation evapotranspiration index (SPEI) value of −0.9. Drought thresholds, however, vary geographically, increasing along the precipitation gradient, potentially due to variations in drought stress‐related gene expression and tolerance strategies across different humidity environments. Therefore, we developed a new autumn phenology model (DMPD) by incorporating a drought threshold parameter that distinguishes contrasting drought effects and predicts future EOPS under two scenarios (SSP245 and SSP585). The DMPD model substantially enhanced the representation of EOPS, as evidenced by a lower root mean square error (RMSE), higher correlation, and a greater proportion of significant correlations with EOPS derived from GOSIF. By the end of the century, EOPS is projected to be consistently delayed under both moderate (SSP245) and high (SSP585) warming scenarios, with the rate of delay decelerating under SSP245 after 2066. Our study confirms that increasing drought intensity leads to contrasting shifts in the autumnal photosynthetic phenology of tropical and subtropical forests and highlights the potential of integrating these contrasting drought effects into phenology models to improve the accuracy of vegetation phenology predictions under future climate change scenarios.

Cxcl9 modulates aging associated microvascular metabolic and angiogenic dysfunctions in subcutaneous adipose tissue - Xin Fu; Yu Zhao; Xiwei Cui; Siyuan Huang; Yanze Lv; Chen Li; Fuxing Gong; Zhigang Yang; Xiaonan Yang; Ran Xiao (Angiogenesis, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic impact of Gracilaria bailinae extracts on photosynthesis and metabolism in Phaeodactylum tricornutum - Li-Gong Zou; Fu-Fang Wen; Xiao Zhang; Gang Li; Qing Wang; Hong-Ye Li; Yu-Feng Yang (Marine Environmental Research, 2025)

Immobilization or mobilization of heavy metal(loid)s in lake sediment-water interface: Roles of coupled transformation between iron (oxyhydr)oxides and natural organic matter - Yuanhang Li; Shaokang Zhang; Hang Fu; Yuheng Sun; Shoujuan Tang; Jinwen Xu; Jun Li; Xiaofeng Gong; Lei Shi (Science of The Total Environment, 2025)

Hepatocellular carcinoma epi-immunotherapy with polyion complex micelles co-delivering HDAC8 inhibitor and PD-L1 siRNA - Jinhua Zhao; Taiqing Liu; Yinqi Li; Xiaodong Yang; Xiaoyu Wang; Yunhai Fu; Yeteng Zheng; Ziying Yao; Jingwen Wang; Hanlin Gong; Zhiyao He (Chemical Engineering Journal, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)

Characteristics and Functions of Rhizosphere Bacterial Communities of Camelli sinensis cv. Shifocui with Cold Resistance Characteristics in Anhui Province, China - Shuiqin Shi; Enhui He; Junjie Ma; Mengrui Ge; Jiahui Gao; Tianyi Peng; Yu Fu; Jianfen Wang; Li Gong; Duoqi Zhou; Yafang Liu (Current Microbiology, 2025)

Ion-exchange induced multiple effects to promote uranium uptake from nonmarine water by micromotors - Linhui Fu; Kai Feng; Qianqian Li; Mengting Qin; Jing Yang; Xinle Zhang; Ling Chen; Jiang Gong; Jinping Qu; Ran Niu (Journal of Hazardous Materials, 2024)

Electron transfer mechanism mediated MOF-derived nanoflowers catalyst for promoting peroxymonosulfate activation and ciprofloxacin degradation - Hao Li; Xiangyi Gong; Hua Tong; Fu Feng; Dajung Ren (Journal of Environmental Chemical Engineering, 2024)

Bandgap-level engineered photodynamic antibacterial film with boosting ROS production for long-term fruit preservation - Bangfeng Fu; Liang Zhang; Peng Zhao; Weijie Gong; Linpin Luo; Bingzhi Li; Xiaoyue Yue; Jianlong Wang; Yiping Chen (Food Packaging and Shelf Life, 2024)

Preparation for a Novel N-Doped Magnetic Sludge-Based Biochar and Application for Norfloxacin Removal from Wastewater - Junming Yi; Dongsheng Feng; Jiangzhe Fu; Yuxin Liu; Ruihui Gong; Peizu Liu; Jing Guo; Kai Cui; Huidong Li (Water, Air, & Soil Pollution, 2024)

Macrophage migration inhibitory factor reversed senescent phenotype in human chondrocytes in vitro - Zhenlan Fu; Qingqing Li; Peiyao Jiang; Xiongbo Song; Junjun Yang; Guangxing Chen; Xiaoyuan Gong; Liu Yang (Molecular Biology Reports, 2024)

Metabolic profile changes of zebrafish larvae in the single- and co-exposures of microplastics and phenanthrene - Jingyi Li; Xiao Liu; Jing Fu; Zhiyuan Gong; Sabrina Yanan Jiang; J. Paul Chen (Science of The Total Environment, 2024)

Study on the integrated technology of arsenic removal and tungsten extraction based on the formation and decomposition of arsenotungstic acid - Caifang Cao; Ailin Fu; Qiuxian Mai; Yong Li; Huaping Nie; Jian Wang; Dandan Gong; Xiaochen Qiu (Chemical Engineering Journal, 2024)

Constructing asymmetric-electron-density Pd-Zn dual-atoms on N-doped defective mesoporous carbon for electrochemical reduction of CO2 - Yanlong Gong; Xiaohong Yang; Ying Zhang; Jingyun Li; Liang Xu; Song Li; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2024)

Moist-electric generators using biomass Juncus effusus fibers with 3D microchannels for wearable applications - Lingling Su; Chunhua Zhang; Wenyang Tang; Zhuan Fu; Junyao Gong; Jieyao Qin; Li Li; Liangjun Xia; Weilin Xu (Chemical Engineering Journal, 2024)

Leveraging chemotherapy-induced PD-L1 upregulation to potentiate targeted PD-L1 degradation using nanoparticle-based targeting chimeras - Yuai Li; Jingwen Wang; Ruilian Yu; Tao Gong; Zhirong Zhang; Renhe Liu; Yao Fu (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Atomically L12 ordered (PtHf)x(NiTi)100-x/CNT as bifunctional catalysts for hydrogen evolution reaction and methanol oxidation reaction with high activity and durability - Yue Fu; Fudi Wang; Chuandong Qing; Yuyuan Zhang; Mingkai Li; Xinghui Cao; Shen Gong; Liuxiong Luo; Zhou Li (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Open-framework indium hexacyanoferrate for high-voltage and coaxially-fibrous aqueous K//Zn battery - Yuxin Li; Chenglong Liu; Wenyuan Zhang; Jinwen Fu; Yongbao Feng; Wenbin Gong; Qiulong Li (Chemical Engineering Journal, 2024)

Novel findings on the mitochondria in ciliates, with description of mitochondrial genomes of six representatives - Tengteng Zhang; Jinyu Fu; Chao Li; Ruitao Gong; Khaled A. S. Al-Rasheid; Naomi A. Stover; Chen Shao; Ting Cheng (Marine Life Science & Technology, 2024)
Determining and comparing mitochondrial genomes (mitogenomes) are essential for assessing the diversity and evolution of mitochondria. Ciliates are ancient and diverse unicellular eukaryotes, and thus are ideal models for elucidating the early evolution of mitochondria. Here, we report on six new mitogenomes of spirotrichs, a dominant ciliate group, and perform comparative analyses on 12 representative species. We show that: (1) the mitogenomes of spirotrichs are linear structures with high A+T contents (61.12–81.16%), bidirectional transcription, and extensive synteny (except for the nad5 , ccmf and cob genes in Euplotia); (2) the non-split of NADH dehydrogenase subunit 2 gene ( nad2 ) is a plesiomorphy of ciliates, whereas it has evolved into a split gene in Spirotrichea (apart from Euplotes taxa), Oligohymenophorea, and Armophorea; (3) the number of small subunit ribosomal proteins (rps) encoded in mitogenomes increases in the later branching classes of ciliates, whereas rps8 shows a loss trend during the evolution of Euplotes taxa; (4) the mitogenomes of spirotrichs exhibit A/T codon bias at the third position, and the codon bias is mainly due to DNA mutation in oligotrichs, hypotrichs and Diophrys appendiculata ; (5) the phylogenetic position of D. appendiculata is unstable and controversial based on both phylogenetic analyses and mitogenome evidence. In summary, we investigated the mitogenome diversity of spirotrichs and broadened our understanding of the evolution of mitochondria in ciliates.

Evidence for low sulfate and anoxic deep waters in early Cambrian - Yizhe Gong; Dandan Li; Menghan Li; Lilin Sun; Xiaolin Zhang; Yawen Cui; Yong Fu; Yilun Xu; Yanan Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Prediction of turn and zigzag maneuvers with the hydrodynamic derivatives obtained by SQCM - Jiaye Gong; Yunbo Li; Fan Jiang; Zheng Fu (Ocean Engineering, 2024)

GNSS NLOS detection method based on stacking ensemble learning and applications in smartphones - Fu Zheng; Qingcheng Li; Jiale Wang; Xiaopeng Gong; Hailu Jia; Chuanming Zhang; Chuang Shi (GPS Solutions, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Silkworm pupae globulin promotes Cordyceps militaris fermentation: Regulation of metabolic pathways enhances cordycepin synthesis and extends the synthesis phase - Yi-Tong Li; Hao-Tian Yao; Ze-Lai Huang; Lu-Chan Gong; Richard A. Herman; Fu-An Wu; Jun Wang (Food Bioscience, 2024)

Mo-Mg isotopes trace the role of serpentinite in generating arc magmatism - Qing-Chen Yang; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun; Bing Gong (Chemical Geology, 2024)

Heavy metal spatial distribution, source analysis, and ecological risks in the central hilly area of Hainan Island, China: results from a high-density soil survey - Jingjing Gong; Jianweng Gao; Hui Wu; Lujun Lin; Jianzhou Yang; Shixin Tang; Zhengliang Wang; Zhuang Duan; Yangang Fu; Yongwen Cai; Shuqi Hu; Yong Li (Environmental Geochemistry and Health, 2024)

Surf-riding and broaching prediction of ship sailing in regular waves by LSTM based on the data of ship motion and encounter wave - Jinya Xu; Jiaye Gong; Yunbo Li; Zheng Fu; Luyao Wang (Ocean Engineering, 2024)

Novel material to enhance the integrity of CCUS cement sheath: Exploration and application of calcium aluminate cement - Peng Gong; Huacai Fu; Dan He; Yuanpeng Wu; Kaiyuan Mei; Chunmei Zhang; Xin He; Tao Liu; Shangdong Li; Xiaowei Cheng (Gas Science and Engineering, 2024)

Modified biochar reduces the greenhouse gas emission intensity and enhances the net ecosystem economic budget in black soil soybean fields - Yidan Gong; Renjie Hou; Qiang Fu; Tianxiao Li; Jinwu Wang; Zhongbin Su; Weizheng Shen; Wenqi Zhou; Yijia Wang; Mo Li (Soil and Tillage Research, 2024)

High-performance plastic-derived metal-free catalysts for organic pollutants degradation via Fenton-like reaction - Yu Hou; Qi Fu; Huajie Zhong; Jiaxing Yu; Yuan Tao; Zeyu Gong; Jianqiang Li; Songbo Wei; Junlang Qiu; Junhui Wang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

The effect of broad bean diet on structure, flavor and taste of fresh grass carp: A comprehensive study using E-nose, E-tongue, TPA, HS-SPME-GC-MS and LC-MS - Bing Fu; Mengping Zheng; Huici Yang; Junming Zhang; Yichao Li; Guangjun Wang; Jingjing Tian; Kai Zhang; Yun Xia; Zhifei Li; Wangbao Gong; Hongyan Li; et al. (Food Chemistry, 2024)

Urbanization effects on the spatial patterns of spring vegetation phenology depend on the climatic background - Peiyi Yin; Xuecao Li; Yuyu Zhou; Jiafu Mao; Yongshuo H. Fu; Wenting Cao; Peng Gong; Wanru He; Baoguo Li; Jianxi Huang; Xiaoping Liu; Zitong Shi; et al. (Agricultural and Forest Meteorology, 2024)

Mo isotopes record recycling of anoxic sediment in a Paleo-oceanic subduction zone - Xiang Fu; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

Differentiating environmental scenarios to establish geochemical baseline values for heavy metals in soil: A case study of Hainan Island, China - Yanling Sun; Jianzhou Yang; Kai Li; Jingjing Gong; Jianweng Gao; Zhenliang Wang; Yongwen Cai; Keqiang Zhao; Shuqi Hu; Yangang Fu; Zhuang Duan; Lujun Lin (Science of The Total Environment, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Effects of heat stress on the chemical composition, oxidative stability, muscle metabolism, and meat quality of Nile tilapia (Oreochromis niloticus) - Yichao Li; Bing Fu; Junming Zhang; Guangjun Wang; Wangbao Gong; Jingjing Tian; Hongyan Li; Kai Zhang; Yun Xia; Zhifei Li; Jun Xie; Gen Kaneko; et al. (Food Chemistry, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Trace elements and Li isotopes distinguish between liquid and solid phases contributing to mafic arc magmas - Li-Tao Ma; Li-Qun Dai; Yong-Fei Zheng; Zi-Fu Zhao; Bing Gong; Yilin Xiao; Fengtai Tong (Lithos, 2023)

Coloration of cotton fibers with inorganic pigments using a transient high-temperature technology - Qimeng Zhu; Zhuan Fu; Liangjun Xia; Xiaofeng Wang; Zhaozixuan Zhou; Dan Sheng; Xinjie Wei; Junyao Gong; Sijie Zhou; Wenbin Li; Chunhua Zhang (Journal of Cleaner Production, 2023)

The dual role of acetate additives among carbon materials functionalized and CH4/N2 separation - Shuohao Li; Shenguang Fu; Yuqing Gong; Yuanping Cheng; Liang Wang (Gas Science and Engineering, 2023)

Study on the Effect of Hull Attitude on the Resistance Reduction of SWATH with Airflow Injection - Dapeng Zhang; Yunbo Li; Jiaye Gong; Zheng Fu (Journal of Marine Science and Engineering, 2023)
With the development of the green ship concept in design and construction, how to reduce the resistance to reduce fuel consumption has become a focus of ship research. As an important drag reduction method, the air lubrication method has been applied to various ship types, but it is still a new method in the study of SWATH (small waterplane area twin hull) drag reduction. In this paper, the air lubrication method is applied to a SWATH model with an overall length of 2.5 m to numerically study the influence of the hull attitude on the air coverage and resistance reduction. The grid is verified by the grid independence and the experiment results. Then, the resistance of the SWATH model under different trim angles and drafts is calculated, and the air coverage on the surface is observed. The drag reduction rates of different areas, including the strut, underwater body, and fins, are analyzed, too. The results show that the slight trim by the head is more conducive to the resistance reduction of the SWATH model, and the resistance reduction rate can reach 39.11%. The draft mainly affects the resistance reduction of the strut, and the difference is more than 10%.

New insight into efficient CH4/N2 separation based on Ni-decorated porous carbon functional composites - Shuohao Li; Shenguang Fu; Yuqing Gong; Liang Wang; Yuxiang Wu; Lei Wang; Yuanping Cheng (Fuel, 2023)

The complexes of soybean protein isolate and procyanidin B2 have synergistic hypolipidemic activity at the cellular level by activating the AMPKα pathway - Lei Ji; Hongling Fu; Yi Wang; Jiaxin Li; Xiaoqing Yang; Hao Gong; Xiangze Meng; Wendan Jing; Weichang Dai; Youbao Li; Bo Lyu; Hansong Yu (Food Chemistry, 2023)

Structure, physicochemical and functional properties of plant-based SPI films from different soybean varieties deficient in β-conglycinin subunits - Jiaxin Li; Khalid Amin; Hongling Fu; Lei Ji; Yi Wang; Hao Gong; Hansong Yu; Bo Lyu; Xiaoqing Yang (Food Packaging and Shelf Life, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Driving forces and their interactions of soil erosion in soil and water conservation regionalization at the county scale with a high cultivation rate - Bang-lin Luo; Jiang-wen Li; Chun-ming Gong; Shou-qin Zhong; Chao-fu Wei (Journal of Mountain Science, 2023)

Host-specific bacterial communities associated with six cold-seep sponge species in the South China Sea - Yan Wang; Lin Gong; Zhaoming Gao; Yong Wang; Feng Zhao; Lulu Fu; Xinzheng Li (Frontiers in Marine Science, 2023)
The cold-seep sponge holobionts are attracting growing attention in recent years. In this study, we utilized 16S rRNA amplicons to characterize the bacterial communities of six deep-sea sponge species found in sponge grounds at the Formosa Ridge cold seep in the South China Sea. Bacterial communities in these geographically proximal sponge species are dominated by Proteobacteria (mainly Gammaproteobacteria and Alphaproteobacteria) but exhibit distinct diversity and compositions among communities. Further analysis revealed that the SUP05 clade (Thioglobaceae) dominated most of the sponge samples. Meanwhile, phylogenetic analysis showed that the six sponge species harbored diverse SUP05 OTU phylotypes, indicating significant divergence within this clade. Additionally, operational taxonomic units (OTUs) of the family Methylomonadaceae, another abundant group in these sponges, displayed a significant genetic distance both from each other and from known species. Our findings support the hypothesis of the host-species specificity of sponge-associated bacterial communities, a widely accepted concept in shallow-water and other deep-sea sponges. The presence of dominant functional microbes, such as sulfur- and methanol-oxidizing bacteria, suggests their crucial role as chemosynthetic symbionts in facilitating the niche adaption of sponge hosts to the cold seep ecosystem. In conclusion, our study reveals the diverse and novel bacterial communities in deep-sea sponges from cold seep environments, contributing new knowledge to the host-species specificity of bacterial communities within sponges and highlighting the potential significance of functional microbes in cold seep ecosystems with dynamic energy supplies.

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Measuring the route topography impact on real driving emissions based on neural network models - Hualong Xu; Li Zhang; Hong Chang; Jinlin Han; Dongmei Wu; Xiangkun Gong; Mingming Fu (Environmental Research, 2023)

Modelling and analysis of the volume change behaviors of Li-ion batteries with silicon-graphene composite electrodes - Xueyan Li; Zhiyuan Zhang; Lili Gong; Kang Fu; Haosong Yang; Chenyang Wang; Peng Tan (Chemical Engineering Journal, 2023)

Research progress and applications of colorful Brassica crops - Fuyan Li; Yingying Gong; Annaliese S. Mason; Qian Liu; Juan Huang; Miao Ma; Meili Xiao; Huadong Wang; Donghui Fu (Planta, 2023)

Molybdenum isotopes record recycling of subducting sediment in active continental margin, Northeast China - Wei Fang; Li-Qun Dai; Xiang Fu; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)

Study on Trimaran's coupled motion states and torsional rolling motion - Yunbo Li; Jiaye Gong; Zheng Fu (Ocean Engineering, 2023)

Composition, Distribution, and Source Apportionment of Organochlorine Pesticides (OCPs) in Soil of a Chemical Industrial Park and its Surrounding in the Northeast of Qinghai-Tibet Plateau - Xiaojun Li; Lixia Cao; Xin Lin; Wanlong Fu; Zongqiang Gong; Xiangfeng Zeng; Huajun Fang; Zhiheng Li (Water, Air, & Soil Pollution, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Accelerated sulfate radical generation from peroxymonosulfate by ZIF-67-derived Co3O4 encapsulated in g-C3N4: A gift from in situ growth - Jinping Liang; Ling Fu; Kai Gao; Ping Zhang; Xiaoguang Duan; Xiaobo Gong; Li Cai (Chemical Engineering Journal, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

An analysis of the main secondary metabolites of Dendrobium nobile revealed three new sesquiterpenoids - Xingyue Chen; Bin Wu; Daoyong Gong; Dezhao Fu; Hongting Qin; Biao Li (Phytochemistry Letters, 2023)

Distinct contribution of aqueous solutions and hydrous melts to the mantle sources: Geochemical evidence from Late Paleozoic igneous rocks in Southwestern Tianshan, Western China - Li-Tao Ma; Li-Qun Dai; Zi-Fu Zhao; Fang Huang; Bing Gong (Lithos, 2023)

Impact of flow velocity on the heterogeneous reaction of SO2 over Fe2O3 - Yangyang Liu; Tao Wang; Qiuyue Ge; Zhuocheng Shi; Kejian Li; Kedong Gong; Lifang Xie; Wei Wang; Qianlong Wang; Jin Han; Hongbo Fu; Jianmin Chen; et al. (Atmospheric Environment, 2023)

Human factors engineering of BCI: an evaluation for satisfaction of BCI based on motor imagery - Xiaotong Lyu; Peng Ding; Siyu Li; Yuyang Dong; Lei Su; Lei Zhao; Anmin Gong; Yunfa Fu (Cognitive Neurodynamics, 2023)

The migration and accumulation of typical pollutants in the growing media layer of bioretention facilities - Yongwei Gong; Xia Li; Peng Xie; Hongyan Fu; Linmei Nie; Junqi Li; Yanhong Li (Environmental Science and Pollution Research, 2023)

The heated-induced gelation of soy protein isolate at subunit level: Exploring the impacts of α and α′ subunits on SPI gelation based on natural hybrid breeding varieties - Hongling Fu; Jiaxin Li; Xiaoqing Yang; Mohammed Sharif Swallah; Hao Gong; Lei Ji; Xiangze Meng; Bo Lyu; Hansong Yu (Food Hydrocolloids, 2023)

Flexible and weavable 3D porous graphene/PPy/lignocellulose-based versatile fibrous wearables for thermal management and strain sensing - Junyao Gong; Wenyang Tang; Liangjun Xia; Zhuan Fu; Sijie Zhou; Jiajing Zhang; Chunhua Zhang; Li Li; Hua Ji; Weilin Xu (Chemical Engineering Journal, 2023)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

Mutation of rpoS is Beneficial for Suppressing Organic Acid Secretion During 1,3-Propandiol Biosynthesis in Klebsiella pneumoniae - Shufan Dong; Xuxia Liu; Tianyu Chen; Xiaoqin Zhou; Shengming Li; Shuilin Fu; Heng Gong (Current Microbiology, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Yohimbine Directly Induces Cardiotoxicity on Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Yiqi Gong; Li Yang; Jun Tang; Jijian Zheng; Nevin Witman; Philipp Jakob; Yao Tan; Minglu Liu; Ying Chen; Huijing Wang; Wei Fu; Wei Wang (Cardiovascular Toxicology, 2022)

Enhanced degradation of reactive brilliant red X-3B by photocatalysis integrated with micro-electrolysis - Gong Cheng; Yibo Zhang; Lei Sun; Jing Wan; Zhang Li; Chenyuan Dang; Jie Fu (Environmental Science and Pollution Research, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Diurnal Variations of Precipitation over the Steep Slopes of the Himalayas Observed by TRMM PR and VIRS - Xiao Pan; Yunfei Fu; Sen Yang; Ying Gong; Deqin Li (Advances in Atmospheric Sciences, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Brain-Wide Shape Reconstruction of a Traced Neuron Using the Convex Image Segmentation Method - Shiwei Li; Tingwei Quan; Hang Zhou; Qing Huang; Tao Guan; Yijun Chen; Cheng Xu; Hongtao Kang; Anan Li; Ling Fu; Qingming Luo; Hui Gong; et al. (Neuroinformatics, 2020)

Growth factor regulatory system: a new system for not truly recognized organisms - Jian Xiao; Zhuofeng Lin; Hua Qin; Zhilong Zheng; Fanghua Gong; Yanlong Liu; Xiaokun Li; Xiaobing Fu (Science China Life Sciences, 2020)

An on-demand construction method of disaster scenes for multilevel users - Weilian Li; Jun Zhu; Yunhao Zhang; Lin Fu; Yuhang Gong; Ya Hu; Yungang Cao (Natural Hazards, 2020)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Identifying Weak Signals in Inhomogeneous Neuronal Images for Large-Scale Tracing of Sparsely Distributed Neurites - Shiwei Li; Tingwei Quan; Hang Zhou; FangFang Yin; Anan Li; Ling Fu; Qingming Luo; Hui Gong; Shaoqun Zeng (Neuroinformatics, 2019)

Extensive changes in gene expression and alternative splicing due to homoeologous exchange in rice segmental allopolyploids - Zhibin Zhang; Tiansi Fu; Zhijian Liu; Xutong Wang; Hongwei Xun; Guo Li; Baoxu Ding; Yuzhu Dong; Xiuyun Lin; Karen A. Sanguinet; Bao Liu; Ying Wu; et al. (Theoretical and Applied Genetics, 2019)

PM2.5 affects establishment of immune tolerance in newborn mice by reducing PD-L1 expression - Li Yan; Caihui Gong; Linyan Ying; Wenlong Fu; Sha Liu; Jihong Dai; Zhou Fu (Journal of Biosciences, 2019)

Anticancer effect of Polyphyllin Ι in colorectal cancer cells through ROS-dependent autophagy and G2/M arrest mechanisms - Si Yu; Lijiao Wang; Zhixing Cao; Daoyin Gong; Qianyi Liang; Hanting Chen; Huizhu Fu; Wenwen Wang; Xue Tang; Zihao Xie; Yang He; Cheng Peng; et al. (Natural Product Research, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

mPGES-1-derived prostaglandin E2 stimulates Stat3 to promote podocyte apoptosis - Jing Yu; Yimei Wu; Lu Wang; Wen Zhang; Man Xu; Jiayu Song; Yu Fu; Yiyun Cui; Wei Gong; Shuzhen Li; Weiwei Xia; Songming Huang; et al. (Apoptosis, 2017)

The increased expression of follicle-stimulating hormone leads to a decrease of fecundity in transgenic Large White female pigs - Kai Jiang; Pan Xu; Wanbo Li; Qiang Yang; Longyun Li; Chuanmin Qiao; Huanfa Gong; Hao Zheng; Zhimin Zhou; Hao Fu; Qiuyan Li; Yuyun Xing; et al. (Transgenic Research, 2017)

Using a global reference sample set and a cropland map for area estimation in China - Le Yu; XueCao Li; CongCong Li; YuanYuan Zhao; ZhenGuo Niu; HuaBing Huang; Jie Wang; YuQi Cheng; Hui Lu; YaLi Si; ChaoQing Yu; HaoHuan Fu; et al. (Science China Earth Sciences, 2017)

Stacked Autoencoder-based deep learning for remote-sensing image classification: a case study of African land-cover mapping - Weijia Li; Haohuan Fu; Le Yu; Peng Gong; Duole Feng; Congcong Li; Nicholas Clinton (International Journal of Remote Sensing, 2016)

Distribution of hepatitis C virus genotypes in volunteer blood donors from Chengdu, China - Tianxiang Gong; Xin Zhao; Yijia Luo; Ying Hong; Shuping Li; Xuemei Fu (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Production of transgenic beef cattle rich in n-3 PUFAs by somatic cell nuclear transfer - Gong Cheng; Changzhen Fu; Hong Wang; C. Adoligbe; Shengjuan Wei; Shijun Li; Bijie Jiang; Hongbao Wang; Linsen Zan (Biotechnology Letters, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Reduction of nitrobenzene with sulfides catalyzed by the black carbons from crop-residue ashes - Wenwen Gong; Xinhui Liu; Li Tao; Wei Xue; Wenjun Fu; Dengmiao Cheng (Environmental Science and Pollution Research, 2014)

Identifying novel salt-tolerant genes from Dunaliella salina using a Haematococcus pluvialis expression system - Wen-fang Gong; Li-na Zhao; Bin Hu; Xi-wen Chen; Feng Zhang; Zheng-mao Zhu; De-fu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Risk assessment of the city water resources system based on Pansystems Observation-Control Model of Periphery - Qiang Fu; Fanli Gong; Qiuxiang Jiang; Tianxiao Li; Kun Cheng; He Dong; Xiaosong Ma (Natural Hazards, 2014)

Is there a role of TNFR1 in acute lung injury cases associated with extracorporeal circulation? - Yu Zhao; Chong-wei Zhang; Wen-jing Zhou; Jiao Chen; Nan-fu Luo; Li-na Gong; Lei Du; Jing Zhou (Journal of Zhejiang University-SCIENCE B, 2014)

Acceleration effect of amino acid supplementation on glycerol assimilation by Escherichia coli in minimal medium - Gang Xiang; Jiang Li; JiFu Duan; Fei Shao; Jiajie Xu; Shuilin Fu; Heng Gong (Biotechnology Letters, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The polymorphisms of LYRM1 gene and their association with body measurement and ultrasound traits of Qinchuan cattle - Yaokun Li; Jianbin Gao; Ning Yang; Changzhen Fu; Gong Cheng; Hongbao Wang; Linsen Zan (Molecular Biology Reports, 2013)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Isolation and characterization of 40 microsatellite loci for oriental river prawn (Macrobrachium nipponense) and cross-species utility - Hui Qiao; Fajun Li; Hongtuo Fu; Yan Wu; Yongsheng Gong; Sufei Jiang; Yiwei Xiong; Ning Wang (Conservation Genetics Resources, 2011)

Two cotton Cys2/His2-type zinc-finger proteins, GhDi19-1 and GhDi19-2, are involved in plant response to salt/drought stress and abscisic acid signaling - Gang Li; Fu-Ju Tai; Yong Zheng; Juan Luo; Si-Ying Gong; Ze-Ting Zhang; Xue-Bao Li (Plant Molecular Biology, 2010)

Construction and Preliminary Analysis of a Deep-Sea Sediment Metagenomic Fosmid Library from Qiongdongnan Basin, South China Sea - Yongfei Hu; Chengzhang Fu; Yeshi Yin; Gong Cheng; Fang Lei; Xi Yang; Jing Li; Elizabeth Jane Ashforth; Lixin Zhang; Baoli Zhu (Marine Biotechnology, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Seasonal changes in tannin and nitrogen contents of Casuarina equisetifolia branchlets - Li-hua Zhang; Gong-fu Ye; Yi-ming Lin; Hai-chao Zhou; Qi Zeng (Journal of Zhejiang University-SCIENCE B, 2009)

Molecular genetic structure and evolution in native and colonized populations of the Chinese mitten crab, Eriocheir sinensis - Chenghui Wang; Sifa Li; Cuizhang Fu; Xiaoling Gong; Len Huang; Xiao Song; Yan Zhao (Biological Invasions, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Chemical composition, antimicrobial and antioxidant activities of the essential oil of Tibetan herbal medicine Dracocephalum heterophyllum Benth - ChunJiang Zhang; HongYu Li; Tian Yun; YongHong Fu; ChunMei Liu; Bu Gong; BenJia Neng (Natural Product Research, 2008)

Relationships between O isotope equilibrium, mineral alteration and Rb–Sr chronometric validity in granitoids: implications for determination of cooling rate - Jiang Feng Chen; Yong-Fei Zheng; Zi-Fu Zhao; Bo Li; Zhi Xie; Bing Gong; Hui Qian (Contributions to Mineralogy and Petrology, 2007)

Oxygen and hydrogen isotope geochemistry of gneisses associated with ultrahigh pressure eclogites at Shuanghe in the Dabie Mountains - Bin Fu; Yong-Fei Zheng; Zhengrong Wang; Yilin Xiao; Bing Gong; Shuguang Li (Contributions to Mineralogy and Petrology, 1999)